Analytic combustion with thermodynamics, chemical kinetics, and mass transfer - Date, Anil W. (Anil Waman) (Cambridge University Press, 2011)
"Combustion involves change in the chemical state of a substance from a fuel-state to a product-state via chemical reaction accompanied by release of heat energy. Design or performance evaluation of equipment also requires knowledge of the RATE of change of state. This rate is governed by the laws of thermodynamics and by the empirical sciences of heat and mass transfer, chemical kinetics and fluid dynamics. Theoretical treatment of combustion requires integrated knowledge of these subjects and strong mathematical and numerical skills.ANALYTIC COMBUSTION is written for advanced undergraduates, graduate students and professionals in mechanical, aeronautical, and chemical engineering. Topics were carefully selected and presented to facilitate learning with emphasis on effective mathematical formulations and solution strategies. The book features over 60 solved numerical problems and analytical derivations and nearly 145 endof- chapter exercise problems. The presentation is gradual starting from Thermodynamics of Pure and Mixture substances, Chemical Equilibrium, building to a uniquely strong chapter on Application Case-Studies"--